2019
DOI: 10.1111/aogs.13781
|View full text |Cite
|
Sign up to set email alerts
|

Manual perineal protection: The know‐how and the know‐why

Abstract: Manual perineal protection is an obstetric intervention to mitigate the risk of perineal trauma. There are two effective techniques (Finnish and Viennese) with minor but distinctive differences in between them. The main aim of this study was to explore clinicians’ knowledge about the manual perineal protection technique they use. The study took place in three maternity units that support manual perineal protection policy in three European countries (Czech Republic, Slovenia and the UK). Our study demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…However, it is important to highlight that the use of the non-dominant hand to control the speed of head expulsion is an integral part of both the Finnish and Viennese MPP (please refer to Table 1 and supplementary video in our commentary). 2 We also share the same opinion as Levin and colleagues that maintaining We concur with Levin et al that in studies where the assessment of OASIS is one of the outcomes of interest, it would be prudent for this to be carried out by an independent assessor. A maternity healthcare professional trained to perform structured assessment of the perineum and anorectal complex would be best suited to do so rather than someone from a different discipline, which is impractical, particularly as many births take place outside a multidisciplinary hospital setting.…”
Section: Slowing Of Fetal Head Descent Is An Integral Component Of Masupporting
confidence: 76%
“…However, it is important to highlight that the use of the non-dominant hand to control the speed of head expulsion is an integral part of both the Finnish and Viennese MPP (please refer to Table 1 and supplementary video in our commentary). 2 We also share the same opinion as Levin and colleagues that maintaining We concur with Levin et al that in studies where the assessment of OASIS is one of the outcomes of interest, it would be prudent for this to be carried out by an independent assessor. A maternity healthcare professional trained to perform structured assessment of the perineum and anorectal complex would be best suited to do so rather than someone from a different discipline, which is impractical, particularly as many births take place outside a multidisciplinary hospital setting.…”
Section: Slowing Of Fetal Head Descent Is An Integral Component Of Masupporting
confidence: 76%
“…Effective MPP is a complex procedure to execute [17][18][19][20][21]. Indeed, a recent survey of practitioners from units that support a routine MPP policy demonstrated that only 5.6% of respondents were able to provide a comprehensive description of MPP correctly [18,19]. The Finnish technique of MPP (FMPP) involves application of the thumb and index finger of the dominant hand on the perineal skin anterolateral to the fourchette and their approximation to reduce midline perineal strain.…”
Section: Introductionmentioning
confidence: 99%
“…The flexed middle finger is used to apply pressure against the perineal body to facilitate the process of fetal head extension. While, the non-dominant hand controls the speed of fetal head expulsion and facilitates fetal head extension [18,19]. Practically, it is difficult to evaluate the actual contribution of the individual components of FMPP in a clinical setting, because of a high number of confounders and obstetric variables, some of which are hardly quantifiable.…”
Section: Introductionmentioning
confidence: 99%
“…Effective MPP is a complex procedure to execute [17][18][19][20][21]. Indeed, a recent survey of practitioners from units that support a routine MPP policy demonstrated that only 5.6% of respondents were able to provide a comprehensive description of MPP correctly [18,19]. The Finnish technique of MPP (FMPP) involves application of the thumb and index nger of the dominant hand on the perineal skin anterolateral to the fourchette and their approximation to reduce midline perineal strain.…”
Section: Introductionmentioning
confidence: 99%
“…The exed middle nger is used to apply pressure against the perineal body to facilitate the process of fetal head extension. While, the nondominant hand controls the speed of fetal head expulsion and facilitates fetal head extension [18,19].…”
Section: Introductionmentioning
confidence: 99%